Alveolysis in primary teeth associated with dental trauma: Case report (Research, Society and Development, 2020)
Alveolysis is characterized as the resorption of the alveolar bone with subsequent exposure of primary tooth root in the oral cavity. The objective of this study was to report a clinical case of a 6-year-old female patient, who attended the Primary Health Care in an inland city of Paraíba, with alveolysis after dental trauma. Clinical examination revealed the presence of alveolysis in the teeth 51 and 52 with lesion characterized by the mobility of dental elements and an extensive gingival vertical lesion in the vestibular region (51). The indicated treatment was extraction of both teeth and clinical follow-up for the others. The clinical conduct started with a psychological adaptation of the patient because she had suffered a trauma and still felt pain in the region. It is concluded that, in the case of a dental emergency, it is necessary to remove primary teeth with alveolysis, thus, avoiding injuries to subsequent permanent teeth and adjacent soft tissues. Pediatric dentistry needs more case reports on this subject so that the etiology and clinical conduct can follow the precepts of evidence-based dentistry.